(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Drug waste and inefficiencies in pharmaceutical supply chains contribute to significant economic losses and environmental harm. Pharmacists play a crucial role in minimizing drug waste through inventory optimization, proper medication management, and patient education. This paper explores strategies pharmacists can employ to enhance supply chain efficiency, reduce unnecessary drug disposal, and promote sustainable practices. Key interventions include just-in-time inventory systems, medication therapy management, and collaboration with healthcare providers. The findings highlight the pharmacist’s impact on cost savings, environmental sustainability, and improved patient outcomes.